The Home of Fairy Tales: The Dragon’s Den - Vaz da Silva, Francisco (Ways of Dwelling: Crisis, Craft, Creativity. 13th Congress of Société Internationale d’Ethnologie et de Folklore (SIEF), 2017)
This talk addresses the "home" of fairy tales on two different levels. First, it points out that the geographical home of fairy tales includes North Africa and the Near East as well as the Indo-European realm. To bring this point home, I address a group of North-African berber tales that meaningfully converse with both the Eastern and the Western European traditions. Second, I look at the dragon's dwelling at the core of fairy tales. Vladimir Propp famously proposed that the archetype of the fairy tale—the "one tale with respect to which all fairy tales will appear as variants"—comprises the abduction of a princess by a dragon. That is, because a dragon kidnapped the princess the hero departs to save her. This insight entails that a maiden's abduction is the prime mover of the fairy tale. Yet, whatever happens in the dragon's den remains enshrouded in mystery. I propose to carefully pry a little. I ask: What happens in the dragon's den? Could a girl ever call it home? What is "home" in the universe of fairy tales?